Constructing a built-in electric field by anchoring highly dispersed Zn single atoms on UiO-66-NH2 for efficient CO2 photoreduction. Issue 44 (13th October 2022) - Chu, Mingna; Li, Yang; Chen, Ximing; Hou, Guangyao; Zhou, Yan; Kang, Hongjun; Qin, Wei; Wu, Xiaohong
Abstract : Efficient CO2 conversion has been realized on UiO-66-NH2 -0.7Zn SAs benefitting from the formation of the built-in electric field by anchoring Zn single atoms (SAs) on UiO-66-NH2 . Abstract : Solar-driven carbon dioxide (CO2 ) reduction into valuable chemicals or feedstock is of great significance for the sustainable development of the environment and energy. Herein, we presented a photo-induced reduction method to synthesize catalysts by anchoring Zn single atoms (SAs) on UiO-66-NH2 . Impressively, UiO-66-NH2 -0.7Zn SAs had excellent performance in converting CO2 to carbon monoxide (CO), which was about a 5-fold improvement compared to pristine UiO-66-NH2 without a photosensitizer or hole sacrificial agent under UV-vis light. The remarkable photocatalytic CO2 reduction performance was attributed to the built-in electric field construction by anchoring highly dispersed Zn SAs on UiO-66-NH2 . The built-in electric field could effectively promote the separation of photogenerated charges and activate CO2 . Density functional theory (DFT) calculations revealed that low-coordination Zn–N2 sites could dramatically enhance the formation of COOH*, which was the rate-limiting step for CO generation. This study created a new opportunity to develop high-efficiency photocatalysts containing single-atom sites for photocatalytic CO2 reduction.